Brachystele guayanensis is a Cyclopogon (Orchidaceae): notes on its biology and taxonomy - Meneguzzo, Thiago E. C.; Carvalho, Bruno M. De; Batista, João A. N.; Gomes, Sueli M.; Proença, Carolyn E. B. (Phytotaxa, 2024)
Brachystele guayanensis is hereby transferred to the genus Cyclopogon based on molecular systematics and morphological evidence. The major change in the circumscription of Cyclopogon with the inclusion of this species is an increase in the number of flowers per inflorescence, a reduction in flower size, and the fact that sepals may become petaloid.